Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk - Komai, Tomoyuki; Matsuzaki, Koji; Hibino, Mai (Zootaxa, 2016)
A poorly known thorid shrimp, Lebbeus longidactylus (Kobjakova, 1936), is redescribed on the basis of material collected from the Nemuro Strait, southwestern part of the Sea of Okhotsk, at depths of 600–800 m. The newly collected samples represent the second finding of this rarely collected species since the type description. The species belongs to the informal species group characterized by the possession of epipods on maxilliped 3 to pereopod 2, and appears close to L. scrippsi Wicksten & Méndez, 1982, known from the eastern Pacific, in that the slender dactyli of pereopods 3–5 each terminate in a simple, non-biunguiculate tip and by having accessory spiniform setae restricted to the proximal half of the flexor margin. The elongate rostrum with more numerous dorsal spines, more numerous dorsolateral spiniform setae on the telson, and a single spine on the dorsodistal margin of article 1 of the antennular peduncle readily differentiate L. longidactylus from L. scrippsi.